PENGARUH ECONOMIC VALUE ADDED TERHADAP TOBIN Q DENGAN MARKET VALUE ADDED SEBAGAI VARIABEL INTERVENING - Sri Hermuningsih (Jurnal Ekonomi dan Bisnis, 2018)
This study aims to analyze the effect of Economic Value Added on Tobin Q with Market Valueadded as intervening variable. The sample of this research is a manufacturing company listed onIndonesia Stock Exchange in 2011-2016. Data analysis using regression analysis. The resultsshowed that Economic Value Added did not affect Tobin Q and Market Value added (MVA)effect on Tobin Q. Market Value Added (MVA) did not become intervening variable betweenEVA and Tobin Q. Market Value added are not mediate Economic Value Added to Tobin QKeywords: Economic Value Added, Market Value Added, Firm Value